WRITTEN TELEPHONING GUIDELINES FOR THE OPERATORS OF LOTUS GARDEN HOTEL KEDIRI - Yenny Wong; Julia Eka Rini (Kata Kita: Journal of Language, Literature, and Teaching, 2015)
These guidelines are made to solve telephoning behaviour problems at Lotus Garden Hotel. The explanation is in Indonesian because it can help the operators who do not speak English to know how to telephone well step by step so that they really understand about what they will do when they are telephoning with the customers. The second purpose is to help to get a plus impression for Lotus Garden Hotel. The guidelines consist of receiving calls, making calls, leaving messages, taking messages, and dealing with the problems. It also includes the forms that the operators can use in leaving messages, taking messages, and dealing with the problems to the customers in telephoning. The guidelines will help the front office department where operators usually belong to.